1996
DOI: 10.1006/faat.1996.0171
|View full text |Cite
|
Sign up to set email alerts
|

Specific Antibody Responses to Subtilisin Carlsberg (Alcalase) in Mice: Development of an Intranasal Exposure Model

Abstract: An intranasal (i.n.) dosing model was developed in mice as a potential alternative to more difficult, time-consuming, and costly guinea pig intratracheal (GPIT) or mouse intratracheal models for assessment of the respiratory immunogenicity of detergent enzymes. Using a benchmark enzyme, Alcalase (protease subtilisin Carlsberg), studies were conducted to standardize the model in terms of mouse strain, dosing and serum harvest regimen, and the primary immunoglobulin endpoint to use. The primary assay endpoint se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 52 publications
0
10
0
2
Order By: Relevance
“…Furthermore, IgG1 in mice is an anaphylactic antibody (Oshiba et al, 1996), but only in combinations with high allergen doses (Finkelman et al, 2005). IgG1 is co-regulated with IgE via the IL-4/Th2 path- way (Purkerson and Isakson, 1992), which may explain the use of IgG1 to assess immunogenicity or adjuvant effects in several murine systems (Kimber et al, 2003;Robinson et al, 1996;Yanagisawa et al, 2006) and as a risk factor for developing an IgE response in humans. Overall, the extent to which the IgG1 response should be considered a protective response or a risk factor for development of IgE is not clear at present.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, IgG1 in mice is an anaphylactic antibody (Oshiba et al, 1996), but only in combinations with high allergen doses (Finkelman et al, 2005). IgG1 is co-regulated with IgE via the IL-4/Th2 path- way (Purkerson and Isakson, 1992), which may explain the use of IgG1 to assess immunogenicity or adjuvant effects in several murine systems (Kimber et al, 2003;Robinson et al, 1996;Yanagisawa et al, 2006) and as a risk factor for developing an IgE response in humans. Overall, the extent to which the IgG1 response should be considered a protective response or a risk factor for development of IgE is not clear at present.…”
Section: Discussionmentioning
confidence: 98%
“…Animals were held either upright or in a supine position while dosing solutions (20 or 50 µl divided equally between the 2 nares) were administered (Robinson et al, 1996). Drops were placed outside of each naris and inhaled by the mouse.…”
Section: Intranasal Instillation Of Dyesmentioning
confidence: 99%
“…Intranasal administration has been used routinely to immunize mice to a variety of viral, fungal, and proteinaceous agents, providing superior results to intratracheal dosing regimens (Nikulin et al, 1997). Others have demonstrated that intranasal administration of proteins to mice elicits specific immunoglobulin E (IgE) and/or IgG responses (Robinson et al, 1996). Few studies have employed intranasal dosing with chemicals.…”
mentioning
confidence: 99%
“…The intranasal instillation of allergens (ie, Schistosoma mansoni egg antigen, Aspergillus fumigatus) has been used to successfully induce features of allergic rhinitis (18,24). In addition, the intranasal instillation of allergens has been used to elicit antibody responses for the identification of the respiratory sensitization potential of detergent enzymes in the mouse intranasal test (MINT) (3,20). Our exposure regimen differed from the MINT protocol in the schedule and duration of allergen dosing.…”
mentioning
confidence: 99%
“…Our exposure regimen differed from the MINT protocol in the schedule and duration of allergen dosing. The MINT protocol includes instillations on days 1, 3, and 10 followed by sacrifice on day 15 (3,20). Our study consisted of 5 intranasal instillations during a distinct sensitization phase followed by the first challenge (single intranasal instillation) 2 weeks later and a second challenge 10 days after the first challenge followed by sacrifice from 24 to 96 hours after final instillation.…”
mentioning
confidence: 99%